Vector-Valued Inequalities for Commutators of Singular Integrals on Herz Spaces with Variable Exponents (Communications in Mathematical Research, 2019)
Based on the theory of variable exponents and BMO norms, we prove thevector-valued inequalities for commutators of singular integrals on both homogeneousand inhomogeneous Herz spaces where the two main indices are variable exponents.Furthermore, we show that a wide class of commutators generated by BMO functionsand sublinear operators satisfy vector-valued inequalities.